2017
DOI: 10.1103/physrevb.96.094405
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of magnetic properties in the vicinity of the Verwey transition in Fe3O4 thin films

Abstract: We have systematically studied the evolution of magnetic properties, especially the coercivity and the remanence ratio in the vicinity of the Verwey transition temperature (TV ), of high-quality epitaxial Fe3O4 thin films grown on MgO (001), MgAl2O4 (MAO) (001), and SrTiO3 (STO) (001) substrates.We observed rapid change of magnetization, coercivity, and remanence ratio at TV , which are consistent with the behaviors of resistivity versus temperature [ρ(T )] curves for the different thin films. In particular, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 76 publications
1
13
1
Order By: Relevance
“…However, it has been demonstrated that the electronic and magnetic properties of magnetite films can be modified using SrTiO 3 substrates [34,35,36], despite the large lattice mismatch of −7.5%. One advantage of using SrTiO 3 substrates is the possibility of doping and, thus, a tunable conductivity providing either an insulating or metallic substrate which can be used as a bottom electrode in capacitor-like structures [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been demonstrated that the electronic and magnetic properties of magnetite films can be modified using SrTiO 3 substrates [34,35,36], despite the large lattice mismatch of −7.5%. One advantage of using SrTiO 3 substrates is the possibility of doping and, thus, a tunable conductivity providing either an insulating or metallic substrate which can be used as a bottom electrode in capacitor-like structures [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Fe 3 O 4 /NiO bilayers on both substrates, there are a number of works on electronic structure, interfacial coupling, and magnetic characterization [41,42,43,44], whereas to the best of our knowledge there are no detailed structural studies for these bilayers on SrTiO 3 . However, the magnetic and transport characteristics of such films are sensitive to structural variations, number of defects, or stoichiometric deviations, and can be affected by the strain between film and substrate [36]. Therefore, in this work, a comprehensive structural characterization of Fe 3 O 4 /NiO bilayers of different thicknesses grown on Nb-doped SrTiO 3 (001) and for comparison on MgO(001) is presented.…”
Section: Introductionmentioning
confidence: 99%
“…8 In epitaxial Fe 3 O 4 films grown on MgO, Al 2 O 3 , and SrTiO 3 substrates, the mis-stacking of the Fe 3 O 4 lattice on a substrate at the first stage of nucleation could form antiphase boundaries (APBs) which preserve the electronic and magnetic properties of Fe 3 O 4 films away from its bulk one. [9][10][11][12][13][14][15] Across APBs, magnetic moments are coupled antiferromagnetically. 16,17 The spin interaction under the magnetic field across APB is considered to illustrate the MR in Fe 3 O 4 .…”
mentioning
confidence: 99%
“…1998; Liu et al. 2017) and the remanence held by magnetite after cooling through (Özdemir and Dunlop 1999; Özdemir 2000; Heider et al. 1992; King and Williams 2000).…”
Section: Introductionmentioning
confidence: 99%